2017
DOI: 10.1074/mcp.m116.061903
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Labeling with Amino Acids (SILAC)-Based Proteomics of Primary Human Kidney Cells Reveals a Novel Link between Male Sex Hormones and Impaired Energy Metabolism in Diabetic Kidney Disease

Abstract: Male sex predisposes to many kidney diseases. Considering that androgens exert deleterious effects in a variety of cell types within the kidney, we hypothesized that dihydrotestosterone (DHT) would alter the biology of the renal tubular cell by inducing changes in the proteome. We employed stable isotope labeling with amino acids (SILAC) in an indirect spike-in fashion to accurately quantify the proteome in DHT-and 17␤-estradiol (EST)-treated human proximal tubular epithelial cells (PTEC). Of the 5043 quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 92 publications
(84 reference statements)
3
19
0
Order By: Relevance
“…penicillin, and 50g/ml streptomycin, as previously described. 37 All the experiments were performed at passage 5. After reaching ~70% confluence, cells were serum-starved for 16h and treated with 20ng/µL of TNFα, 1,000U/mL of IFNγ, or 1ng/µL of lipopolysaccharide (LPS) (all from Sigma) for 24h.…”
Section: Cell Culture Human Glomerular Microvascular Endothelial Cellsmentioning
confidence: 99%
“…penicillin, and 50g/ml streptomycin, as previously described. 37 All the experiments were performed at passage 5. After reaching ~70% confluence, cells were serum-starved for 16h and treated with 20ng/µL of TNFα, 1,000U/mL of IFNγ, or 1ng/µL of lipopolysaccharide (LPS) (all from Sigma) for 24h.…”
Section: Cell Culture Human Glomerular Microvascular Endothelial Cellsmentioning
confidence: 99%
“…We demonstrated that the androgen dihydrotestosterone (DHT), but not the estrogen estradiol (EST), increased enzymes involved in glucose and glutamine metabolism in PTECs. These changes were confirmed in healthy and diabetic male mice and related to kidney injury 31 . We thus postulated that energy metabolism could be the key to understand sex hormone-related effects in kidney physiology and pathophysiology.…”
Section: Introductionmentioning
confidence: 52%
“…We and others have demonstrated that functional and metabolic alterations in DKD develop in a sex-specific fashion [31][32][33][34][35][36][37][38][39][40][41][42] . Sex chromosomes define physiological features in adult somatic tissues 43 , and influence the development of cardiovascular disease 44 , but little is known about the effect of cell sex on kidney metabolism and disease.…”
Section: Introductionmentioning
confidence: 91%
“…Interest in the inclusion of sex as a consideration in uremic pruritus disease is bolstered by well-established relationships between sex and itch-related mechanisms. Mast cells express androgen and estrogen receptors and respond to sex hormones, 116 - 118 and mast cell number and degranulation are sex-dependent. 119 , 120 Moreover, male and female mast cells are transcriptionally different and respond differently to stress.…”
Section: Reviewmentioning
confidence: 99%